Geochemical characterisation and petrogenesis of the Polat Granitoid in Eastern Taurus Belt, Turkey - Önal, A; Bingöl, AF (Geological Soc India, 2000)
The Eastern Taurus Belt represents a collision zone between Cimmerian and the Arabian continents. Along this orogenic belt, metamorphics, ophiolitic rocks and are magmatics occur widely. The Polat Granitoid, whose size is approximately 80 so. km (length 24, width 3.5), is located to the west of Malatya in this belt. This granitoid comprises plutonic rocks such as diorite, quartzdiorite, monzodionite, tonalite, granodiorite and other intrusive rocks. There are many mafic enclaves (ME) seen within the granitoids. Based on field, petrographical and geochemical data, this granitoid is classified into two clusters viz; diorite and tonalite. The diorite shows SiO2, variation from 52.47 to 57.80 % and tonalite from 61.40 to 68.00 %. The differentiation index (D1) varies from 22.73 to 49.15 for diorite and from 59.40 to 68.12 for tonalite. All samples plot in the subalkalic field. Most of them are calc alkaline and all of them belong to middle-lower K Magma Series. CaO-Y trends indicate either a constant or a slight increase in Y value. TiO2,- Zr relationship does not show a clear fractionation trend. But, a regular TIO2, decrease and the low Ni and Cr abundance can be explained by minor biotite and hornblende fractionation. All samples fall within the VAG field. Low TiO2, concentrations of samples (generally <1%) are consistent with other are-derived rocks. ORG-normalised geochemical patterns are observed to be similar to Chilean type are granitoids. Polat Granitoid shows features similar to calc alkaline granitoids, which were emplaced in continental or island arcs above subduction zones. This granitoid was developed as a product of an island are which was near the Malatya-Keban platform in late Cretaceous. The magma is formed by the melting of the subducted slab. Presence of a skarn zone between the metamorphics and granitoids indicates that this are was not far from the continental platform.
Keywords: geochemistry; petrogenesis; Polat Granitoid; Taurus Belt; Turkey